Women's outcomes following mixed-sex, women-only, and home-based cardiac rehabilitation participation and comparison by sex - Fiorella A. Heald; Susan Marzolini; Tracey J. F. Colella; Paul Oh; Rajni Nijhawan; Sherry L. Grace (BMC, 2021)
Abstract Background Despite women's greater need for cardiac rehabilitation (CR), they are less likely to utilize it. Innovative CR models have been developed to better meet women's needs, yet there is little controlled, comparative data assessing the effects of these models for women. This study compared outcomes in women electing to participate in mixed-sex, women-only, or home-based CR, and a matched sample of men. Methods In this retrospective study, electronic records of CR participants in Toronto who were offered the choice of program model between January 2017 and July 2019 were analyzed; clinical outcomes comprised cardiorespiratory fitness, risk factors and psychosocial well-being. These were assessed at intake and post-6-month program and analyzed using general linear mixed models. Results There were 1181 patients (727 women [74.7% mixed, 22.0% women-only, 3.3% home-based]; 454 age and diagnosis-matched men) who initiated CR; Cardiorespiratory fitness among women was higher at initiation of mixed-sex than women-only (METs 5.1 ± 1.5 vs 4.6 ± 1.3; P = .007), but no other outcome differences were observed. 428 (58.9%) women completed the programs, with few women retained in the home-based model limiting comparisons. There were significant improvements in high-density lipoprotein cholesterol (P = .001) and quality of life (P = .001), and lower depressive symptoms (P = .030) as well as waist circumference (P = .001) with mixed-sex only. VO2peak was significantly higher at discharge in mixed-sex than women-only (estimate = 1.67, standard error = 0.63, 95% confidence interval = 0.43-2.91). Conclusion Participation in non-gender-tailored women-only CR was not advantageous as expected. More research is needed, particularly including women participating in home-based programs.